THE RELATIONSHIP BETWEEN PHYSICAL-CHEMICAL CHARACTERISTICS AND BIOLOGICAL ACTIVITY OF PEPTIDE 562—572 OF LUTEINIZING HORMONE RECEPTOR MODIFIED BY DECANOYL RADICALS AT THE N- AND C-TERMINI - Sphakova, E A; Sorokoumov, V N; Akenti’ev, A V; Derkach, K V; Tennikova, T B; Shpakov, A O (T͡S︡itologii͡a, 2017)
Lipophilic derivatives of peptides corresponding to the cytoplasmic regions associated with the G-protein coupled receptors (GPCRs) are capable of functioning as an intracellular agonist. Previously, we have shown that peptides corresponding to region 562—572 of luteinizing hormone receptor (LHR) and modified by decanoate and palmitate at the C-terminus activate adenylyl cyclase (AC) in the testes of rats. The stimulating effect of peptide 562—572 modified by decanoates at the N- and C-termini (IV) peaked at a concentration of 10(–5) M and then subsequently decreased with increasing concentration. We hypothesized that this may be due to ability of the peptide IV to micelle formation. To test this suggestion, we examined the relationship between biological activity, hydrophobicity and ability to micelle formation for peptide IV and other acylated derivatives of peptide 562—572 including the derivatives containing C-terminal decanoate (III) and palmitate (VI). It has been shown that the stimulating effect of peptide IV at a concentration of 10(–5) M on AC activity in the plasma membranes of rat testes and ovaries is only slightly inferior to that of peptide VI and superior to the corresponding effect of peptide III. The effect of peptide IV at a concentration of 10–3 M was reduced by 20—27 % and amounted to 50—51 and 87—88 % of that of peptides VI and III, respectively. Despite the high hydrophobicity, the peptide IV had abnormally low retention time in reverse-phase HPLC when it was eluted from the Nucleosil C8 column, even lower than that of unmodified peptide 562—572. However, with increasing concentration of trifluoroacetic acid in the eluent from 0.1 to 0.5 % causing the destruction of micelle-like structures, the retention time of the peptide IV was significantly increased, whereas it remained unchanged in the case of the other peptides. Surface tension of aqueous solution of peptide IV insignificantly decreased with the increase of its concentration, but then, at peptide concentration of 710(–6) M, the sharp decline and the plateau were found, which indicates the beginning of the formation of micelles. Thus, at concentration of 10(–5) M and higher the peptide IV forms micelles which prevents its interaction with the receptor. The ability of GPCR-peptides to self-aggregation and micelle formation should be taken into account when developing their membrane-active analogues.